Developing Reading E-Module Based on Langkat Sultanate History for English Department Study of STKIP Al-Maksum Langkat - Marpaung, Fernando De Napoli; Rosmen, Rosmen (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
Providing English learning material with developing reading E-Module Based on Langkat Sultanate History is important as English Department Study of STKIP Al-Maksum Langkat. This research aims to develop Reading e-Module Based on Langkat Sultanate History, to increase students’ awareness about Langkat Sultanate History and to promote local wisdom at Langkat District. This research is concerned with the development of an English reading e-Module for students of the English department study of STKIP Al-Maksum by applying the four phase Research and Development (R & D) proposed by Gall, Gall & Borg (2003). At the define stage, first, the author decides to create the requirements to create the e-Module following the need analysis. Furthermore, at the design stage, the author creates the initial design (prototype) e-Module. The results of the study show that the module that has been developed is valid, practical and effective. The validity of the module reaches a valid category based on the expert’s and validator’s evaluation. It is hoped that they will be able to continue to raise local culture or local wisdom in Indonesia as a learning module to preserve Indonesian culture for students.